Randomized Trial of Acute Changes in Plasma Phosphate After Phosphorus-Standardized Meals in Peritoneal Dialysis - Martin Thorbjørn Lundin; Iain Bressendorff; Bent Kristensen; Niklas Rye Jørgensen; Rizwan Butt; Ditte Hansen (Kidney International Reports, 2021)
Introduction: Hyperphosphatemia is associated with increased morbidity and mortality in patients with chronic kidney disease. The aim of this study was to assess whether a meal with high phosphorus content would affect plasma phosphate in the hours that follow among subjects with end-stage kidney disease on peritoneal dialysis. Methods: This was a single-blinded randomized cross-over trial of 12 subjects on maintenance peritoneal dialysis, in which subjects were randomized to consume a meal with either high or low phosphorus content on 2 separate trial days. On each trial day, plasma phosphate was measured immediately before consumption of the standardized meal and after 1, 2, 3, and 5 hours. Results: The mean fasting plasma phosphate at baseline was 1.69 ± 0.22 mmol/l. Plasma phosphate was similar between the 2 meals at baseline, as well as at 1, 2, 3, and 5 hours after consumption. The largest observed difference in plasma phosphate between the 2 meals was 0.15 mmol/l, which occurred 5 hours after consumption (high-phosphorus meal 1.75 ± 0.32 mmol/l vs. low-phosphorus meal 1.60 ± 0.14 mmol/l (P = 0.06)). Using summary analyses for repeated measures, we observed a significant difference in the plasma phosphate between the 2 meals (P = 0.03). Conclusion: Our results show that in subjects with end-stage kidney disease, a meal with high phosphorus content has only a negligible effect on plasma phosphate compared to a meal with low phosphorus content. Thus, large increases in plasma phosphate cannot be accounted for by a high intake of phosphorus in the hours before blood sampling.